2013
DOI: 10.4274/mirt.135
|View full text |Cite
|
Sign up to set email alerts
|

Co-existent Paget’s Disease of the Bone, Prostate Carcinoma Skeletal Metastases and Fracture on Skeletal Scintigraphy-Lessons to be Learned

Abstract: Bone scintigraphy, despite being non-specific, is a very sensitive and simple investigation for patients with active Paget’s disease of the bone. Skeletal metastases and Paget’s disease may co-exist in the elderly patients as both conditions are commonly seen in this age group. Clinical and radiological correlation may help to improve the diagnostic specificity of a bone scintigram. We report a patient in whom concurrent Paget’s disease and a rib fracture became evident only on repeat scintigraphy following su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Pagetic bone can be hard to differentiate from metastases,[ 21 ] especially since Paget's disease of bone and osseous metastases often coexist. [ 22 ] This possibility must be considered to avoid mistaken diagnosis and ensure the correct staging and treatment of patients. The patients in this study demonstrated typical imaging findings: osteolytic areas, cortical thickening, loss of distinction between cortex and medulla, trabecular thickening, osteosclerosis, bone expansion, and bone deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Pagetic bone can be hard to differentiate from metastases,[ 21 ] especially since Paget's disease of bone and osseous metastases often coexist. [ 22 ] This possibility must be considered to avoid mistaken diagnosis and ensure the correct staging and treatment of patients. The patients in this study demonstrated typical imaging findings: osteolytic areas, cortical thickening, loss of distinction between cortex and medulla, trabecular thickening, osteosclerosis, bone expansion, and bone deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Among the previously published cases that reported coexistence of PDB and metastatic bone disease, the primary sites of malignancy were the breast, lung, and prostate. [18][19][20][21] In our patient, the final diagnosis of metastatic bone disease secondary to adenocarcinoma of the lung was found after PDB was diagnosed by bone biopsy. As illustrated in the case, three modalities, including radiography, bone biopsy and 18 F-FDG PET/CT were utilized in the diagnostic process.…”
Section: Discussionmentioning
confidence: 88%
“…[ 3 ] Paget’s disease also tends to preserve anatomic details while metastatic disease tends to obscure anatomy. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%